Echocardiographic diastolic abnormalities of the left ventricle in inflammatory joint disease. Issue 4 (April 1991) - Rowe, I F; Gibson, D G; Keat, A C; Brewerton, D A
Abstract : Echocardiographic early diastolic abnormalities have been shown recently in 50% of men with ankylosing spondylitis. Similar techniques were used to investigate subjects with rheumatoid arthritis and psoriatic arthritis with or without spondylitis. These subjects had no clinical, radiographic, or electrocardiographic evidence of cardiac or respiratory disease. Echocardiographic abnormalities seen resembled those of ankylosing spondylitis in that the interval between minimum left ventricular dimension and mitral valve opening was prolonged in 12 of 22 subjects with rheumatoid arthritis and in seven of 11 subjects with psoriatic arthritis. Isovolumic relaxation time was significantly prolonged in four subjects with rheumatoid arthritis and one with psoriatic arthritis. Unlike ankylosing spondylitis, however, there was consistent reduction in peak rate of left ventricular dimension increase in subjects with rheumatoid arthritis and psoriatic arthritis. In addition, the dimension increase during atrial systole was greater than normal in nine subjects with rheumatoid arthritis and two with psoriatic arthritis. The most likely cause of these abnormalities is increased connective tissue deposition in the myocardium.